Ciências da Funcionalidade Humana e Sustentabilidade Ambiental: a junção das partes constitui o todo? - Schmidt, Maria Luiza Gava [UNESP]; Del-Masso, Maria Cândida Soares [UNESP] (My University, 2014)
The content of this article addresses two complex issues that concern contemporary society: Science of Human Functioning and Environmental Sustainability. On the one hand, the Science of Human Functioning, meeting the principles of the International Classification of Functioning (ICF) and Universal Design, aim the development of accessible projects, products and environments, used by everyone, at the greatest extent possible, free from adaptation or plans to remove architectural barriers. The Universal Design is a process for creating products that are accessible to everyone, regardless their personal characteristics, age, skills and needs. On the other hand, Environmental Sustainability, with principles already imbricated in the Science of Human Functioning, traverses towards the acquisition of realistic measures for the segments of human activities. Based on the emphasis of the sustainable development, it aims to meet current needs not compromising the possibility of future generations to meet their own needs. Thus, it seeks the balance in coexistence between men and the environment by taking care of environmental, social and economic aspects and seeking for alternatives to support life on Earth with no harm to the quality of the planet in the future. It is argued that the combination of the issues contains relevant potential for interdisciplinary action, bringing together professionals from several fields of knowledge that, by socializing their experiences aiming at improving the human functioning and quality of life of people and environment, will be able to innovate and reinvent the knowledge for benefiting welfare, thus contributing effectively to society.

Este artigo tem como objetivo discutir duas temáticas complexas que preocupam a sociedade contemporânea : Ciências da Funcionalidade Humana e Sustentabilidade Ambiental. Por um lado, as Ciências da Funcionalidade Humana, atendendo aos princípios da Classificação Internacional de Funcionalidade (CIF) e do Desenho Universal, objetivam o desenvolvimento de projetos, produtos e ambientes acessíveis, usados por todos, na sua máxima extensão possível, sem necessidade de adaptação ou projeto de eliminação de barreiras arquitetônicas. O desenho universal é um processo para criação de produtos que são acessíveis a todas as pessoas independente de suas características: pessoais, idade, habilidades e necessidades. Por outro lado, a Sustentabilidade Ambiental, com princípios já imbricados nas Ciências da Funcionalidade Humana, versa em prol da aquisição de medidas que sejam realistas para os setores das atividades humanas. Pautada na ênfase do desenvolvimento sustentável visa atender às necessidades do meio ambiente sem comprometer as gerações futuras. Assim, busca o equilíbrio na convivência entre o homem e o meio ambiente ao cuidar dos aspectos ambientais, sociais e econômicos e buscar alternativas para eliminar riscos e sustentar a vida sem prejudicar a qualidade do planeta no futuro. Discute-se que o imbricamento das temáticas contém um relevante potencial para atuação interdisciplinar, com a congregação de profissionais de várias áreas do conhecimento que ao socializarem suas experiências com vistas a melhorar a funcionalidade humana e a qualidade de vida das pessoas e do meio ambiente, poderão inovar e re-inventar o conhecimento em prol do bem-estar, contribuindo efetivamente para a sociedade.
Science of human functioning and environmental sustainability: does the combination of the parts constitute the whole?
Keywords: Ciências da Funcionalidade Humana